2021
DOI: 10.22146/jpkm.41510
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment of Posyandu Cadres in Early Detection of Child Growth Problems: Optimization of KIA Books

Abstract: Posyandu (integrated health center) as a health information center for the community is expected to be the spearhead of early detection of developmental disorders in children under five. Posyandu activities are driven by cadres. Cadres monitor the growth of children under five through anthropometric measurements: body weight, height, head circumference and development milestones. Knowing how to measure anthropometric parameters, data plotting on a growth chart in the Maternal and Child Health (Kesehatan Ibu da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
1
0
3
Order By: Relevance
“…Multivariate analysis also shows that the short course significantly affects after controlling by age, education, occupation, and years of experience. The previous study showed that most cadres had good knowledge about the early detection of malnutrition in children [31], [32]. Furthermore, education level increases their capacity, knowledge, ability, and skill of monitoring growth and development [11,13,33].…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis also shows that the short course significantly affects after controlling by age, education, occupation, and years of experience. The previous study showed that most cadres had good knowledge about the early detection of malnutrition in children [31], [32]. Furthermore, education level increases their capacity, knowledge, ability, and skill of monitoring growth and development [11,13,33].…”
Section: Discussionmentioning
confidence: 99%
“…Kegiatan yang dilakukan di Posyandu lebih mendekatkan pada upaya promotif dan peventif khususnya pelayanan kesehatan dasar: peningkatan kesehatan ibu dan anak (KIA), status gizi masyarakat, imunisasi, keluarga berencana, dan pencegahan dan penanggulangan diare (Hayati and Fatimaningrum 2017;Kementerian Kesehatan RI 2011). Tiap Posyandu dikelola dan dimotori oleh kader posyandu (Muntafiah et al 2021).…”
Section: Pendahuluanunclassified
“…Peran pentingnya adalah sebagai kepanjangan tangan dari Puskesmas dan garda terdepan pelayanan kesehatan masyarakat. Kader merupakan ujung tombak kegiatan Posyandu (Marufah et al 2022;Muntafiah et al 2021). Pelayanan Posyandu oleh kader dapat memberikan dampak positif terhadap peningkatan derajat kesehatan masyarakat.…”
Section: Pendahuluanunclassified
“…Meskipun pandemi, anak anak tetap harus dapat bertumbuh kembang. Anak anak merupakan generasi penerus, yang akan menentukan masa depan bangsa (Muntafiah et al, 2021;Santosa et al, 2019). Di tengah situasi pandemi ini, penyelenggaraan transfer pengetahuan secara online pada masyarakat luas dirasa perlu dilakukan, meskipun dengan segala kelebihan dan keterbatasannya.…”
Section: Gambar 1 Flyer Kegiatan Pengabdian Masyarakatunclassified